An empirical line list for methane near 1 µm (9028–10, 435 cm−1). (November 2015) - Béguier, S.; Liu, A.W.; Campargue, A.
Abstract: The highly congested absorption spectrum of methane near 1 µm was recorded by Fourier Transform Spectroscopy at room temperature. The detectivity threshold of the recordings corresponds to an intensity cut off on the order of 2×10 −26  cm/molecule. An empirical line list is constructed for the 9028–10, 435 cm −1 spectral region. It consists of ( i ) 7212 lines in the 9520–10, 435 cm −1 interval corresponding to the tetracontad and ( ii ) 574 lines in the 9028–9200 cm −1 interval corresponding to the high energy region of the triacontad, dominated by the 3 ν 3 band near 9046 cm −1 . The first line list fills an important gap in the HITRAN database. The obtained data set constitutes a solid basis for future rovibrational assignments on the basis of advanced theoretical methods. Highlights: The FTS methane absorption spectrum is recorded near 1 µm. The first empirical line list is constructed in the tetracontad (9523–10, 435 cm −1 ). The 3ν3 region near 9047 cm −1 (9028–9200 cm −1 ) is revisited.